Relationship between serum uric acid levels and osteoporosis - Rong Xu; Difei Lian; Yan Xie; Lin Mu; Yali Wu; Zhilei Chen; Baoyu Zhang (Endocrine Connections, 2023)
Osteoporosis (OP) is a systemic bone disease in which bone density and quality decrease and bone fragility increases due to a variety of causes, making it prone to fractures. The development of OP is closely related to oxidative stress. Uric acid (UA) is the end product of purine metabolism in the human body. Extracellular UA has antioxidant properties and is thought to have a protective effect on bone metabolism. However, the process of UA degradation can lead to intracellular oxidative stress, which together with UA-induced inflammatory factors, leads to increased bone destruction. In addition, UA can inhibit vitamin D production, resulting in secondary hyperparathyroidism and further exacerbating UA-associated bone loss. This review summarizes the relationship between serum UA levels and bone mineral density, bone turnover markers, and so on, in the hope of providing new insights into the pathogenesis and treatment of OP.